Augmented reality supported work instructions for onsite facility maintenance - Neges, Matthias; Koch, Christian (2016)
During the operation and maintenance phase of buildings operators need to perform on site maintenance activities to prevent functional failures of technical equipment. As this phase is the longest and most expensive one respective improvements can significantly reduce the overall lifecycle budget. Based on their previous work, in this paper the authors present an Augmented Reality (AR) based concept and implementation to support mobile and onsite maintenance activities by (1) preparing and generating AR work order instructions based on Product Lifecycle Management (PLM) information, (2) using these to aid the actual onsite maintenance job using hybrid 3D tracking, and (3) creating enhanced and context-related maintenance service reports to be fed back to the PLM system. Preliminary results reveal the potential of the proposed solution, but also leave room for future improvements.